Amine-Appended Hyper-Crosslinked Polymers for Direct Air Capture of CO2. - Spreng,TL; Danaci,D; Ram,PD; Williams,DR; Pini,R; Petit,C (ACS Sustain Chem Eng, 2026)
Capturing CO2 from the ambient atmosphere is a promising method to reduce the impact of climate change. Fast deployment and scale-up of adsorption-based direct air capture (DAC) technologies are needed to meet the IPCC target and rely, in part, on the development of efficient and scalable low-cost adsorbents. While a benchmark DAC adsorbent, the polymeric resin Lewatit VP OC 1065, has been established, the reasons behind its performance and the potential for further optimization remain largely unknown. Indeed, a fundamental understanding of the relationship between adsorbent pore structure, chemistry, and DAC performance, both equilibrium and kinetics, has yet to be formulated. Here, we have built on the chemistry of Lewatit and synthesized a hyper-crosslinked polymer (HCP) by grafting a microporous chlorine-functionalized support with diethylenetriamine. We produced four different adsorbents by varying the polymerization duration between 10 min and 19 h to assess the impact of pore structure on CO2 uptake at 400 ppm. Reduced degrees of polymerization (i.e., shorter polymerization durations) resulted in higher accessible micropore volume and consequentially increased CO2 uptake and amine efficiency. The best sample achieved an equilibrium uptake of 0.43 mmol/g (400 ppm of CO2, 298 K), which is about half that of the benchmark adsorbent Lewatit VP OC 1065. We have then assessed the CO2 sorption kinetics of this sample (grain size of 24-74 μm) at 400 ppm and 303 K using a gravimetric technique and have compared the results to those of other amine-grafted polymeric adsorbents. We measured a lower bound linear driving force constant (k LDF) of 0.0120 ± 0.0004 s-1. This value is 5.5 times faster than that of the benchmark adsorbent Lewatit VP OC 1065 with the same grain size of 24-74 μm, highlighting the importance of macropore diffusion in addition to the CO2 reaction kinetics. This study shows how synthesis operating conditions alter the pore structures an